A power cable
By using nitrile-based silicone modified white carbon black and compatibilizer in power cables, the problem of insufficient heat resistance and strength of power cables is solved, and the effect of significantly improving heat resistance and strength is achieved.
Patent Information
- Application Number
- CN202410499765.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-04-24
- Publication Date
- 2025-02-28
- Estimated Expiration
- 2044-04-24
AI Technical Summary
The heat resistance of existing power cables needs to be further improved, especially the application of white carbon black in power cables. Due to the dehydration and condensation reaction of silicon hydroxyl groups on the surface, it is difficult to disperse in polymer matrix, affecting its heat resistance and strength.
The white carbon black is modified with nitrile silicone, and the crosslinking degree of the material and the compatibility of the white carbon black with the matrix are improved by adding HDPE-g-MAH and aminohydroxymethyl compounds, thereby improving the heat resistance and strength of the power cable.
Through the use of nitrile-based silicone modified white carbon black and compatibilizer, the heat resistance and strength of the power cable are significantly improved, the agglomeration problem of white carbon black in the power cable is solved, and the overall performance of the product is improved.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of power cables, and in particular to a power cable. Background Art
[0002] Power cable is a special cable used to transmit and distribute electrical energy. Its structure includes conductor, insulation layer, shielding layer and sheath layer. Conductors are usually made of copper and aluminum, insulation layer and sheath layer are usually made of rubber, plastic and other organic materials, and shielding layer is usually made of semiconductor materials, which plays the role of uniform electric field. Its application fields are very wide, including construction, transportation, energy and many other fields.
[0003] With the advancement of technology and the growth of energy demand, the requirements for power cables are also increasing, especially heat resistance. The heat resistance of existing power cables needs to be further improved. Summary of the invention
[0004] The present invention provides a power cable, which solves the problem of poor heat resistance of the power cable in the related art.
[0005] The technical solution of the present invention is as follows:
[0006] A power cable comprises a conductor, an insulating layer, a shielding layer and a sheath layer; the insulating layer is a cross-linked polyethylene insulating layer; and the sheath layer is a polyolefin composite material layer.
[0007] As a further technical solution, an insulating layer is arranged outside the conductor, a shielding layer is arranged outside the insulating layer, and a sheath layer is arranged outside the shielding layer.
[0008] As a further technical solution, the conductor is made of aluminum alloy, and the shielding layer is made of copper wire.
[0009] As a further technical solution, the raw materials of the polyolefin composite material layer include the following components in parts by mass: 100 parts of polyolefin, 40 parts of EPDM rubber, 10 parts of silicone resin, 20-30 parts of flame retardant, 40-60 parts of nitrile siloxane-modified white carbon black, 1.5-3.5 parts of antioxidant, 0.5-1.5 parts of vulcanizer, and 1-2 parts of accelerator.
[0010] The invention adopts nitrile siloxane to modify white carbon black. The nitrile siloxane reacts with the silanol groups on the surface of the white carbon black to solve the problem that a large number of silanol groups exist on the surface of the white carbon black, dehydration condensation between the silanol groups easily causes the white carbon black to agglomerate itself to form aggregate particles, which are difficult to disperse in a polymer matrix, thus greatly reducing the effect of the white carbon black in improving the heat resistance of the power cable. The invention achieves the effect of improving the heat resistance and strength of the power cable prepared from the white carbon black.
[0011] As a further technical solution, the polyolefin includes polyethylene and / or polypropylene.
[0012] As a further technical solution, the raw materials of the nitrile siloxane-modified white carbon black include white carbon black and nitrile siloxane compounds in a mass ratio of 1:0.1-0.3.
[0013] As a further technical solution, the preparation method of the nitrile siloxane-modified white carbon black comprises the following steps: mixing white carbon black with a solvent, adding a nitrile siloxane compound while stirring, and drying to obtain the nitrile siloxane-modified white carbon black.
[0014] As a further technical solution, the nitrile-based siloxane compound includes one or more of 4-(diethoxy-methylsilyl)butyronitrile, 2-triethoxysilylpropionitrile, and 2-(triethoxysilyl)butyronitrile.
[0015] As a further technical solution, the invention also includes 2 to 7 parts of a compatibilizer, wherein the compatibilizer includes HDPE-g-MAH and an aminomethylol compound.
[0016] The present invention adds HDPE-g-MAH and aminomethylol compounds, wherein the HDPE in the HDPE-g-MAH has good compatibility with a polyolefin matrix, the MAH in the HDPE-g-MAH can react with the amino group in the aminomethylol compounds; the hydroxymethyl in the aminomethylol compounds can react with the nitrile group on the surface of nitrile siloxane-modified white carbon black, thereby improving the crosslinking degree of the material and the compatibility of the white carbon black with the matrix, thereby further improving the heat resistance and strength of the power cable prepared from the white carbon black.
[0017] As a further technical solution, the mass ratio of the polyethylene to the compatibilizer is 20:1.
[0018] As a further technical solution, the mass ratio of the HDPE-g-MAH to the aminomethylol compound is 0.3:0.7~0.7:0.3.
[0019] As a further technical solution, the aminohydroxymethyl compound includes 4-amino-2-(hydroxymethyl)phenol and / or 5-amino-1,3-dihydroxymethylbenzene, preferably 5-amino-1,3-dihydroxymethylbenzene.
[0020] As a further technical solution, the flame retardant includes magnesium hydroxide and / or aluminum hydroxide;
[0021] The antioxidant includes one or more of antioxidant 168, antioxidant 1076, and antioxidant 1010;
[0022] The vulcanizing agent includes sulfur and / or peroxide;
[0023] The accelerator includes accelerator CZ and / or accelerator H.
[0024] The working principle and beneficial effects of the present invention are:
[0025] The present invention provides a power cable, comprising a conductor, an insulating layer, a shielding layer and a sheath layer; wherein the insulating layer is made of cross-linked polyethylene; the sheath layer is made of a polyolefin composite material, which not only has good heat resistance and strength, but also has simple process, short production cycle and low cost. DETAILED DESCRIPTION
[0026] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0027] In the following examples and comparative examples: polyethylene is HDPE 3364; polypropylene is PP F401; ethylene propylene diene monomer rubber is EPDM 4725P; silicone resin is silicone resin 623; white carbon black is 800 mesh precipitated white carbon black, SiO 2 Content (on dry basis) ≥98wt%, specific surface area 230~250m 2 / g; HDPE-g-MAH is American DuPont Fusabond E265 HDPE-g-MAH.
[0028] A power cable comprises an aluminum alloy core as a conductor, a cross-linked polyethylene as an insulating layer, a shielding layer made of copper wire and a polyolefin composite material as a sheath layer; the polyolefin composite material is prepared by the following method:
[0029] Example 1
[0030] S1. Mix 60 g of white carbon black with 1.3 L of water, raise the temperature to 60° C., add 12 g of 2-(triethoxysilyl)butyronitrile while stirring, continue stirring for 2.5 h, filter, and dry to obtain nitrile-siloxane-modified white carbon black;
[0031] S2. 100 parts of polyethylene, 40 parts of EPDM rubber, 10 parts of silicone resin, 25 parts of magnesium hydroxide, 50 parts of nitrile siloxane-modified white carbon black, 2.5 parts of antioxidant 168, 1 part of sulfur, and 1.5 parts of accelerator H were mixed at 200° C. and kneaded for 30 min. The mixture was transferred to a 180 r / min twin-screw extruder and extruded at 240° C. to obtain a polyolefin composite material.
[0032] Example 2
[0033] S1. Mix 60 g of white carbon black with 1.3 L of water, raise the temperature to 55° C., add 6 g of 4-(diethoxy-methylsilyl)butyronitrile while stirring, continue stirring for 3 h, filter, and dry to obtain nitrile-siloxane-modified white carbon black;
[0034] S2. 100 parts of polypropylene, 40 parts of EPDM rubber, 10 parts of silicone resin, 20 parts of aluminum hydroxide, 40 parts of nitrile siloxane-modified white carbon black, 1.5 parts of antioxidant 1076, 0.5 parts of sulfur and 1 part of accelerator CZ were mixed at 200° C. and kneaded for 30 min. The mixture was then transferred to a 180 r / min twin-screw extruder and extruded at 240° C. to obtain a polyolefin composite material.
[0035] Example 3
[0036] S1. Mix 60 g of white carbon black with 1.3 L of water, raise the temperature to 65° C., add 18 g of 2-triethoxysilyl propionitrile while stirring, continue stirring for 2 h, filter, and dry to obtain nitrile siloxane-modified white carbon black;
[0037] S2. 100 parts of polyethylene, 40 parts of EPDM rubber, 10 parts of silicone resin, 20 parts of magnesium hydroxide, 10 parts of aluminum hydroxide, 60 parts of nitrile siloxane-modified white carbon black, 3.5 parts of antioxidant 1010, 1.5 parts of benzoyl peroxide, 1 part of accelerator CZ and 1 part of accelerator H were mixed at 200° C. and kneaded for 30 min. The mixture was then transferred to a twin-screw extruder at 180 r / min and extruded at 240° C. to obtain a polyolefin composite material.
[0038] Example 4
[0039] S1. Mix 60 g of white carbon black with 1.3 L of water, raise the temperature to 60° C., add 12 g of 2-(triethoxysilyl)butyronitrile while stirring, continue stirring for 2.5 h, filter, and dry to obtain nitrile-siloxane-modified white carbon black;
[0040] S2. 100 parts of polyethylene, 40 parts of EPDM rubber, 10 parts of silicone resin, 25 parts of magnesium hydroxide, 50 parts of nitrile siloxane-modified white carbon black, 0.2 parts of HDPE-g-MAH, 1.8 parts of 5-amino-1,3-dihydroxymethylbenzene, 1682.5 parts of antioxidant, 1 part of sulfur and 1.5 parts of accelerator H were mixed at 200°C and kneaded for 30 minutes, and then transferred to a 180 r / min twin-screw extruder and extruded at 240°C to obtain a polyolefin composite material.
[0041] Example 5
[0042] S1. Mix 60 g of white carbon black with 1.3 L of water, raise the temperature to 60° C., add 12 g of 2-(triethoxysilyl)butyronitrile while stirring, continue stirring for 2.5 h, filter, and dry to obtain nitrile-siloxane-modified white carbon black;
[0043] S2. 100 parts of polyethylene, 40 parts of EPDM rubber, 10 parts of silicone resin, 25 parts of magnesium hydroxide, 50 parts of nitrile siloxane-modified white carbon black, 0.5 parts of HDPE-g-MAH, 4.5 parts of 5-amino-1,3-dihydroxymethylbenzene, 1682.5 parts of antioxidant, 1 part of sulfur and 1.5 parts of accelerator H were mixed at 200°C and kneaded for 30 minutes, and then transferred to a 180r / min twin-screw extruder and extruded at 240°C to obtain a polyolefin composite material.
[0044] Example 6
[0045] S1. Mix 60 g of white carbon black with 1.3 L of water, raise the temperature to 60° C., add 12 g of 2-(triethoxysilyl)butyronitrile while stirring, continue stirring for 2.5 h, filter, and dry to obtain nitrile-siloxane-modified white carbon black;
[0046] S2. 100 parts of polyethylene, 40 parts of EPDM rubber, 10 parts of silicone resin, 25 parts of magnesium hydroxide, 50 parts of nitrile siloxane-modified white carbon black, 0.7 parts of HDPE-g-MAH, 6.3 parts of 5-amino-1,3-dihydroxymethylbenzene, 1682.5 parts of antioxidant, 1 part of sulfur and 1.5 parts of accelerator H were mixed at 200°C and kneaded for 30 minutes, and then transferred to a 180r / min twin-screw extruder and extruded at 240°C to obtain a polyolefin composite material.
[0047] Example 7
[0048] S1. Mix 60 g of white carbon black with 1.3 L of water, raise the temperature to 60° C., add 12 g of 2-(triethoxysilyl)butyronitrile while stirring, continue stirring for 2.5 h, filter, and dry to obtain nitrile-siloxane-modified white carbon black;
[0049] S2. 100 parts of polyethylene, 40 parts of EPDM rubber, 10 parts of silicone resin, 25 parts of magnesium hydroxide, 50 parts of nitrile siloxane-modified white carbon black, 1.5 parts of HDPE-g-MAH, 3.5 parts of 5-amino-1,3-dihydroxymethylbenzene, 1682.5 parts of antioxidant, 1 part of sulfur and 1.5 parts of accelerator H were mixed at 200°C and kneaded for 30 minutes, and then transferred to a 180r / min twin-screw extruder and extruded at 240°C to obtain a polyolefin composite material.
[0050] Example 8
[0051] S1. Mix 60 g of white carbon black with 1.3 L of water, raise the temperature to 60° C., add 12 g of 2-(triethoxysilyl)butyronitrile while stirring, continue stirring for 2.5 h, filter, and dry to obtain nitrile-siloxane-modified white carbon black;
[0052] S2. 100 parts of polyethylene, 40 parts of EPDM rubber, 10 parts of silicone resin, 25 parts of magnesium hydroxide, 50 parts of nitrile siloxane-modified white carbon black, 2.5 parts of HDPE-g-MAH, 2.5 parts of 5-amino-1,3-dihydroxymethylbenzene, 1682.5 parts of antioxidant, 1 part of sulfur and 1.5 parts of accelerator H were mixed at 200°C and kneaded for 30 minutes, and then transferred to a 180 r / min twin-screw extruder and extruded at 240°C to obtain a polyolefin composite material.
[0053] Example 9
[0054] S1. Mix 60 g of white carbon black with 1.3 L of water, raise the temperature to 60° C., add 12 g of 2-(triethoxysilyl)butyronitrile while stirring, continue stirring for 2.5 h, filter, and dry to obtain nitrile-siloxane-modified white carbon black;
[0055] S2. 100 parts of polyethylene, 40 parts of EPDM rubber, 10 parts of silicone resin, 25 parts of magnesium hydroxide, 50 parts of nitrile siloxane-modified white carbon black, 3.5 parts of HDPE-g-MAH, 1.5 parts of 5-amino-1,3-dihydroxymethylbenzene, 1682.5 parts of antioxidant, 1 part of sulfur and 1.5 parts of accelerator H were mixed at 200°C and kneaded for 30 minutes, and then transferred to a 180 r / min twin-screw extruder and extruded at 240°C to obtain a polyolefin composite material.
[0056] Example 10
[0057] S1. Mix 60 g of white carbon black with 1.3 L of water, raise the temperature to 60° C., add 12 g of 2-(triethoxysilyl)butyronitrile while stirring, continue stirring for 2.5 h, filter, and dry to obtain nitrile-siloxane-modified white carbon black;
[0058] S2. 100 parts of polyethylene, 40 parts of EPDM rubber, 10 parts of silicone resin, 25 parts of magnesium hydroxide, 50 parts of nitrile siloxane-modified white carbon black, 4.5 parts of HDPE-g-MAH, 0.5 parts of 5-amino-1,3-dihydroxymethylbenzene, 1682.5 parts of antioxidant, 1 part of sulfur and 1.5 parts of accelerator H were mixed at 200°C and kneaded for 30 minutes, and then transferred to a 180 r / min twin-screw extruder and extruded at 240°C to obtain a polyolefin composite material.
[0059] Comparative Example 1
[0060] 100 parts of polyethylene, 40 parts of EPDM rubber, 10 parts of silicone resin, 25 parts of magnesium hydroxide, 50 parts of white carbon black, 2.5 parts of antioxidant 168, 1 part of sulfur, and 1.5 parts of accelerator H were mixed at 200° C. and kneaded for 30 minutes, and then transferred to a 180 r / min twin-screw extruder and extruded at 240° C. to obtain a polyolefin composite material.
[0061] The polyolefin composite materials obtained in Examples 1 to 10 and Comparative Example 1 were tested for tensile strength before sheath aging with reference to the method in GB / T 2951.11-2008 "General Test Methods for Insulation and Sheath Materials of Electric Cables and Optical Fiber Cables Part 11: General Test Methods for Thickness and Dimension Measurement Mechanical Properties Test"; and the tensile strength of the sheath after aging was tested after heat aging at 100°C for 168h with reference to the method in GB / T 2951.12-2008 "General Test Methods for Insulation and Sheath Materials of Electric Cables and Optical Fiber Cables Part 12: General Test Methods for Thermal Aging Test Method", and the change rate was calculated according to the following formula:
[0062] Change rate (%) = (tensile strength of sheath after aging - tensile strength of sheath before aging) ÷ tensile strength of sheath before aging × 100
[0063] The results are recorded in Table 1.
[0064] Table 1 Strength and heat resistance of polyolefin composites
[0065]
[0066] It can be seen from Table 1 that the polyolefin composite material provided by the present invention has high tensile strength and good heat resistance.
[0067] Compared with Comparative Example 1, Examples 1 to 10 use nitrile siloxane-modified white carbon black, while Comparative Example 1 uses white carbon black. The tensile strength and heat resistance of the polyolefin composite materials obtained in Examples 1 to 10 are better than those in Comparative Example 1, indicating that nitrile siloxane-modified white carbon black can improve the heat resistance and strength of the polyolefin composite material, thereby improving the heat resistance and strength of the power cable prepared from white carbon black.
[0068] Compared with Example 1, Examples 4 to 10 add HDPE-g-MAH and aminohydroxymethyl compounds, while Example 1 does not add HDPE-g-MAH and aminohydroxymethyl compounds. The tensile strength and heat resistance of the polyolefin composite materials obtained in Examples 4 to 10 are better than those in Example 1, indicating that the addition of HDPE-g-MAH and aminohydroxymethyl compounds can further improve the heat resistance and strength of the polyolefin composite materials, thereby further improving the heat resistance and strength of the power cable prepared from white carbon black.
[0069] The tensile strength and heat resistance of the polyolefin composite materials obtained in Examples 7 to 9 are higher than those in Example 5 and Example 10, indicating that when the mass ratio of HDPE-g-MAH to aminomethylol compounds is 0.3:0.7 to 0.7:0.3, the heat resistance and strength of the polyolefin composite materials are further improved, thereby further improving the heat resistance and strength of the power cable prepared from silica.
[0070] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A power cable, characterized in that: It comprises a conductor, an insulating layer, a shielding layer and a sheath layer; the insulating layer is a cross-linked polyethylene insulating layer; the sheath layer is a polyolefin composite material layer; The raw materials of the polyolefin composite material layer include the following components in parts by weight: 100 parts of polyolefin, 40 parts of EPDM rubber, 10 parts of silicone resin, 20-30 parts of flame retardant, 40-60 parts of nitrile siloxane-modified white carbon black, 1.5-3.5 parts of antioxidant, 0.5-1.5 parts of vulcanizer, 1-2 parts of accelerator, and 2-7 parts of compatibilizer, wherein the compatibilizer includes HDPE-g-MAH and aminomethylol compounds.
2. A power cable according to claim 1, characterized in that: An insulating layer is arranged outside the conductor, a shielding layer is arranged outside the insulating layer, and a sheath layer is arranged outside the shielding layer.
3. A power cable according to claim 1, characterized in that: The conductor is made of aluminum alloy, and the shielding layer is made of copper wire.
4. A power cable according to claim 1, characterized in that: The raw materials of the nitrile siloxane-modified white carbon black include white carbon black and nitrile siloxane compounds in a mass ratio of 1:0.1-0.
3.
5. A power cable according to claim 4, characterized in that: The nitrile-based siloxane compound includes one or more of 4-(diethoxy-methylsilyl)butyronitrile, 2-triethoxysilylpropionitrile, and 2-(triethoxysilyl)butyronitrile.
6. A power cable according to claim 1, characterized in that: The mass ratio of the HDPE-g-MAH to the aminomethylol compound is 0.3:0.7 to 0.7:0.
3.
7. A power cable according to claim 6, characterized in that: The aminohydroxymethyl compounds include 4-amino-2-(hydroxymethyl)phenol and / or 5-amino-1,3-dihydroxymethylbenzene.
8. A power cable according to claim 1, characterized in that: The flame retardant includes magnesium hydroxide and / or aluminum hydroxide; The antioxidant includes one or more of antioxidant 168, antioxidant 1076, and antioxidant 1010; The vulcanizing agent includes sulfur and / or peroxide; The accelerator includes accelerator CZ and / or accelerator H.
Citation Information
Patent Citations
Rubber composition, production method and colored tire containing composition
CN107674257A
Low-smoke halogen-free power cable and preparation process thereof
CN115938661A
Crosslinked-polyethylene insulation oxygen-isolation-layer low-smoke halogen-free flame-retardation power cable
CN202650696U